2016
DOI: 10.1080/15384047.2016.1235667
|View full text |Cite
|
Sign up to set email alerts
|

Expression of steroid hormone receptors and its prognostic significance in urothelial carcinoma of the upper urinary tract

Abstract: To assess the expression status of steroid hormone receptors in upper urinary tract urothelial carcinoma (UUTUC), we immunohistochemically stained for androgen receptor (AR), estrogen receptor-a (ERa), ERb, glucocorticoid receptor (GR), and progesterone receptor (PR) in 99 UUTUC specimens and paired nonneoplastic urothelial tissues. AR/ERa/ERb/GR/PR was positive in 20%/18%/62%/63%/16% of tumors, which was significantly lower (except PR) than in benign urothelial tissues [57% (. There were no significant associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 37 publications
7
75
2
Order By: Relevance
“…Indeed, a similar tendency was seen in the expression of androgen receptor (i.e. 42% in bladder tumors [10] vs. 28% in ureteral tumors [8] vs. 11% in renal pelvic tumors [8]) as well as another transcription factor GATA3 (i.e. 86% in bladder tumors [11] vs. 68% in ureteral tumors [12] vs. 36% in renal pelvic tumors [12]) we stained using the same protocol with identical antibodies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Indeed, a similar tendency was seen in the expression of androgen receptor (i.e. 42% in bladder tumors [10] vs. 28% in ureteral tumors [8] vs. 11% in renal pelvic tumors [8]) as well as another transcription factor GATA3 (i.e. 86% in bladder tumors [11] vs. 68% in ureteral tumors [12] vs. 36% in renal pelvic tumors [12]) we stained using the same protocol with identical antibodies.…”
Section: Discussionsupporting
confidence: 52%
“…Immunohistochemical staining was performed on the sections (5 µm thick) from the UUTUC TMA, using a primary antibody to ZKSCAN3 (TA308508; dilution 1:50; OriGene), as we described previously [6,8]. All the stains were manually scored by a single pathologist (H.M.) who was blinded to sample identity.…”
Section: Introductionmentioning
confidence: 99%
“…IHC has detected AR protein signals in 13–55% of bladder or upper urinary tract urothelial tumors [19, 20, 36, 3844, 49–51], which is significantly lower than the positive rates in normal/non-neoplastic urothelial tissues (58–86%) reported by most of respective comparative studies [36, 38, 40, 51]. However, at least three immunohistochemical studies have demonstrated no AR expression in normal urothelium [42, 43, 52].…”
Section: Discussionmentioning
confidence: 99%
“…However, at least three immunohistochemical studies have demonstrated no AR expression in normal urothelium [42, 43, 52]. Significant or insignificant down-regulation of AR expression in high-grade or MI urothelial carcinomas, compared with low-grade or NMI tumors, has also been found [19, 36, 3840, 42, 44, 49–51]. However, several studies showed even slight increases in AR positivity in high-grade and/or MI tumors [20, 41, 51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation